229k views
2 votes
What is 11(3p+5x)+4x-x

User MattyT
by
6.1k points

2 Answers

5 votes
33p+55x+4x-x=33p+58x
User Kevin Yobeth
by
6.0k points
2 votes

The given expression is 11(3 p + 5 x) + 4 x - x

We shall first solve the parenthesis

Now 11 ×3p = 33p and 11 × 5x = 55x

We get

11(3 p + 5 x) + 4 x - x

= 33p + 55x + 4x - x

Now we shall solve the like terms 55x , 4x & -x

55x + 4x = 59 x.

We get

= 33p + 59x -x

And 59x - x = 58x

We get

= 33p + 58x

Hence

11(3 p + 5 x) + 4 x - x = 33p +58x

User Jlstr
by
7.1k points